Identification of criteria for evaluating school buildings - Machado, Eduarda Lauck; Pasdiora, Lívia; Lacerda Santos, Adriana de Paula; Santos Filho, Mauro Lacerda (Revista ALCONPAT, 2022)
The objective of this research is to identify which criteria should be considered in the evaluation of school buildings, through a systematic review of the literature, consultation of government norms and guidelines and consultations with experts. The research was carried out in 3 stages: 1) systematic review of the literature and 2) review of national standards and guidelines to identify criteria and 3) weighting of criteria, through the application of the Delphi method. 70 evaluation criteria were identified, which were grouped into 11 categories and weighted through consultation with experts. The identification of criteria as presented in this research, aims to contribute to the development of techniques and evaluation methods, to later compose a performance standard for school buildings.